1994
DOI: 10.1038/370434a0
|View full text |Cite
|
Sign up to set email alerts
|

A protein complex required for signal-sequence-specific sorting and translocation

Abstract: We have purified a nascent-polypeptide-associated complex (NAC) which prevents short ribosome-associated nascent polypeptides from inappropriate interactions with proteins in the cytosol. NAC binds nascent-polypeptide domains emerging from ribosomes unless a signal peptide is fully exposed. Depletion of cytosolic proteins (including NAC) from ribosomes carrying nascent polypeptides allows the signal recognition particle (SRP) to crosslink to polypeptides irrespective of whether or not they contain signal pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
376
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(415 citation statements)
references
References 30 publications
21
376
0
4
Order By: Relevance
“…This study has identified a number of such potential proteins, including amongst them, NAC and RACK1 homologues. NAC binds to the ribosome in the vicinity of the tunnel exit of the large subunit and modulates co-translational targeting of polypeptides (Wiedmann et al, 1994). The peptide mass fingerprints acquired from the protein samples revealed the presence of at least two isoforms of alpha-NAC and the 2-DE gel pattern indicated that they may be post-translationally modified.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study has identified a number of such potential proteins, including amongst them, NAC and RACK1 homologues. NAC binds to the ribosome in the vicinity of the tunnel exit of the large subunit and modulates co-translational targeting of polypeptides (Wiedmann et al, 1994). The peptide mass fingerprints acquired from the protein samples revealed the presence of at least two isoforms of alpha-NAC and the 2-DE gel pattern indicated that they may be post-translationally modified.…”
Section: Discussionmentioning
confidence: 97%
“…These two spots were identified as being a subunit of the hetero-dimeric nascent-polypeptide associated complex (NAC), a protein that has previously been shown to interact with the large subunit of the ribosome (Wiedmann et al, 1994). A further collection of non-ribosomal protein spots on the acidic section of the 2-DE gel was exceptional in that their intensities increased proportional to the increase of the intensities observed for the ribosomal proteins between the crude and the pure 80S fraction (as can be seen in Figure 1), indicating that these proteins might be factors associated with the ribosomal complex.…”
Section: Detecting Proteins That Associate With the Plant Ribosomementioning
confidence: 99%
“…Nascent polypeptide associated complex (NAC) heterodimer of αNAC (NACA) and βNAC (BTF3b) is characterized as the first cytosolic factor that binds nascent polypeptides emerging from the ribosome and prevents the peptides from incorrectly binding with other cytosolic factors (Wiedmann et al, 1994). This complex is widely conserved from archaea to human.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant translational pause may temporally separate the adjacent regions on the growing nascent polypeptide. Given that proteins can fold cotranslationally with the possible involvement of the ribosome (Phillips, 1966;Baldwin, 1975;Yonath, 1992;Kudlicki et al, 1994;Wiedmann et al, 1994;Brimacombe, 1995), the temporal separation might exert a phenotypic effect on the structural organization of the encoded protein. We show that as much as 70% of the domain boundaries in a set of 37 Escherichia coli proteins with known tertiary structure are coded by slow regions (that encompass slow codons) on mRNA.…”
mentioning
confidence: 99%